2017
DOI: 10.1111/meta.12242
|View full text |Cite
|
Sign up to set email alerts
|

Building A General Theory of Meta‐Argumentation

Abstract: This article presents a critical analysis of the main modern approaches to the problem of meta-argumentation and suggests a method for developing a general conception of meta-argumentation. A set of theoretical-methodological difficulties (aporias) along this path is revealed. Overcoming these aporias would constitute the main steps toward developing the body of a theory of meta-argumentation.Keywords: argumentation, theory of argumentation, metatheory, metaargumentation, models of meta-argumentation, aporia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Hasmik H. Hovhannisyan, proposing the idea that the use of the term "meta" is applicable in the field of argumentation, presented her understanding of meta-argumentation, tried to solve the problem of the relationship between argumentation, meta-argumentation as a theory and meta-theory (Hovhannisyan, H. H., 2007. Later research has revealed the meta-theoretical difficulties (aporias) in the construction and interpretation of theories in the field of modern natural sciences and humanities (Hovhannisyan, H. H. & Djidjian, 2017).…”
Section: Elements Of the Argumentative Discoursementioning
confidence: 99%
“…Hasmik H. Hovhannisyan, proposing the idea that the use of the term "meta" is applicable in the field of argumentation, presented her understanding of meta-argumentation, tried to solve the problem of the relationship between argumentation, meta-argumentation as a theory and meta-theory (Hovhannisyan, H. H., 2007. Later research has revealed the meta-theoretical difficulties (aporias) in the construction and interpretation of theories in the field of modern natural sciences and humanities (Hovhannisyan, H. H. & Djidjian, 2017).…”
Section: Elements Of the Argumentative Discoursementioning
confidence: 99%